2021
DOI: 10.3390/nano11081964
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Electrochemical Characterization of Electropolymerized Polydopamine Films: Influence of the Deposition Process

Abstract: Polydopamine (PDA) is a synthetic eumelanin polymer which is, to date, mostly obtained by dip coating processes. In this contribution, we evaluate the physical and electrochemical properties of electrochemically deposited PDA films obtained by cyclic voltammetry or pulsed deposition. The obtained PDA thin films are investigated with respect to their electrochemical properties, i.e., electron transfer (ET) kinetics and charge transfer resistance using scanning electrochemical microscopy and electrochemical impe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 56 publications
(101 reference statements)
1
17
0
Order By: Relevance
“…8 nm (inset in Figure 8b). Similar behavior was observed in the work of Kund et al 59 Diffuse reflectance spectra and KM functions show that as the PDA thickens, absorption in the visible range is more pronounced and the band-to-band absorption edge plummets (Figure 8b,c).…”
Section: Influence Of Pda Thickness On Optical and Photoelectrochemic...supporting
confidence: 88%
See 1 more Smart Citation
“…8 nm (inset in Figure 8b). Similar behavior was observed in the work of Kund et al 59 Diffuse reflectance spectra and KM functions show that as the PDA thickens, absorption in the visible range is more pronounced and the band-to-band absorption edge plummets (Figure 8b,c).…”
Section: Influence Of Pda Thickness On Optical and Photoelectrochemic...supporting
confidence: 88%
“…The thickness of PDA depends on many factors such as the solvent, ionic environment, and synthetic approach, 11,12,58,59 which have a profound role in the properties of the semiconductor|PDA heterojunctions. 23,25 In our work, the thickness of the PDA electropolymerized in TiO 2 is almost linearly dependent on the number of CV cycles during electropolymerization with the limiting value of ca.…”
Section: Influence Of Pda Thickness On Optical and Photoelectrochemic...mentioning
confidence: 99%
“…Electrochemical behaviour of the pDA/AuNPs/SPCE 3.1.1. pDA deposition. The electrochemical deposition of polydopamine (pDA) on conductive substrates can be achieved through cyclic voltammetry 38,39 or pulsed deposition, 40,41 both of which are fast-coating processes that offer excellent control over lm thickness. While pDA lm growth via auto-oxidation or dipcoating typically takes several hours, electrochemically deposited pDA lms can be obtained with reproducible thickness and morphology within a few minutes.…”
Section: Resultsmentioning
confidence: 99%
“…The literature 55,61 has shown that when the pH value is greater than 7, dopamine can rely on the dissolved oxygen in the solution to generate polydopamine, which becomes easier under electrooxidation conditions. 62,63 Therefore, it can be inferred that the addition of Li 2 CO 3 leads to the continuous increase of pH (from 7.47 to 9.73), which promotes the formation of polydopamine and leads to electrode passivation. This passivation effect exceeds the deprotonation effect, so that the dopamine oxidation peak current decreases in alkaline media.…”
Section: Simultaneous Determination Of Da and LI 2 Comentioning
confidence: 99%